HUBUNGAN PERSEPSI SISWA TENTANG KOMPETENSI PEDAGOGIK DAN PROFESIONAL GURU DENGAN PRESTASI BELAJAR - Rumiasih Rumiasih; Sumadi Sumadi; Rahma Kurnia Sri Utami (JPG (Jurnal Penelitian Geografi), 2014)
The study aimed to analyze the relationship of, 1) students' perceptions of pedagogical and professional competence of teachers simultaneously with academic achievement, 2) students' perceptions of teachers' pedagogical competence and academic achievement and, 3) students' perceptions of teachers' professional competence and academic achievement. The method of research is correlational. The study population was all students of class XI IPS totaled 76 students. Engineering samples using proportional random sampling. Sample technique is using product moment correlation analysis. The results show that 1) there is a positive relationship between students' perceptions of pedagogical and professional competence of teachers simultaneously with academic achievement. 2) there is a positive relationship between students 'perceptions of teachers' pedagogical competence and academic achievement. 3) there is a positive relationship between students 'perceptions of teachers' professional competence and academic achievementPenelitian bertujuan menganalisis hubungan, 1) persepsi siswa tentang kompetensi pedagogik dan profesional guru secara bersamaan dengan prestasi belajar, 2) persepsi siswa tentang kompetensi pedagogik guru dengan prestasi belajar dan, 3) persepsi siswa tentang kompetensi profesional guru dengan prestasi belajar. Metode penelitian adalah korelasional. Populasi penelitian adalah seluruh siswa kelas XI IPS berjumlah 76 siswa. Teknik sampel menggunakan proporsional random sampling. Teknik analisis menggunakan korelasi product moment. Hasil penelitian menunjukkan 1) ada hubungan positif antara persepsi siswa tentang kompetensi pedagogik dan profesional guru secara bersamaan dengan prestasi belajar. 2) ada hubungan positif antara persepsi siswa tentang kompetensi pedagogik guru dengan prestasi belajar. 3) ada hubungan positif antara persepsi siswa tentang kompetensi profesional guru dengan prestasi belajar.Kata kunci: kompetensi guru, persepsi, prestasi belajar.